The role of trimethylamine N-oxide in disease pathogenesis and the therapeutic potential of traditional Chinese medicine - Qin, Zizhen; Wu, Wanning; Yang, Xinyu; Wang, Xiao; Ding, Anni; Huang, Yueyi; Tang, Jiaxuan; Jiang, Siyuan; Zhang, Peng; Qian, Chenwei; Zhang, Xiangrui; Zhou, Shihan; et al. (Frontiers in Pharmacology, 2025)
Trimethylamine N-oxide (TMAO), a metabolite derived from gut microbiota, has been implicated in the pathogenesis of various chronic diseases, including cardiovascular, digestive, neurological, and renal disorders. This review explores the complex mechanisms by which TMAO contributes to disease progression, including its role in inflammation, oxidative stress, and metabolic disorders. The study focused on the potential of traditional Chinese medicine (TCM) to regulate TMAO levels and mitigate its adverse effects. TCM interventions, through modulation of gut microbiota and inhibition of key enzymes like flavin-containing monooxygenase 3 (FMO3), offer promising therapeutic avenues. Despite the positive outcomes observed in preliminary studies, further research is needed to fully elucidate the mechanisms by which TCM interacts with TMAO and to establish its efficacy in clinical settings.